International law - Janis, Mark W. (New York : Wolters Kluwer, 2021)
"Treatise on International Law for law students"--
The nature of international law -- Treaties -- Custom and other sources of international law -- International law and municipal law -- International courts -- States and international law -- International organizations and regimes -- Individuals and international law -- International law and the international economy -- International conflict of laws.
BIBINDX
Keywords: International law